Assessment of electrosurgical hemostasis and morphological changes in thyroid function in perifocal areas of influence of high-frequency current. - Bodnar, T. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. According to the literature data, there are no comparative characteristics of morphological changes after application of scalpel for tissue dissection and ligation of vessels with atraumatic thread and monopolar and bipolar coagulation. Objective. To demonstrate the feasibility of electrosurgical coagulation in surgery of the thyroid gland. Methods. The study was conducted on 80 laboratory rats. Studied animals were divided into groups according to the surgical intervention methods. Results were analyzed with histological methods on the 3rd, 7th and 14th days. Results. Histological examination of soft tissues in the area of wound on the third postoperative day showed pronounced inflammatory reaction against the foreign body. The inflammatory infiltrate had spread to the thyroid tissue. In general morphological changes were characterized by non-specific aseptic necrosis and development of granulation tissue at the site of coagulation. Conclusion. This analysis of wounds healing shows the benefits of using thermal factor in thyroid surgery over classic dissection with scalpel and vascular ligation with atraumatic thread.